2020
DOI: 10.31729/jnma.4720
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction Level among Patients Treated with Fixed Dental Prosthesis in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Dental treatment aims at correction of existing disease; prevention of future diseasewith rehabilitation of patient’s lost functional capacity and aesthetics. Fixed dental prosthesis is anyprosthesis that is cemented to a natural tooth or dental implants abutments that cannot be removedby patient. The success of prosthodontic treatment is related to prosthesis survival, with its ability tofulfil biologic and patient-evaluated objectives with patient satisfaction. This study is aimed to findthe pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Another documented variable in the present study is patient satisfaction, which is crucial for evaluating the quality of treatment and clinical results from a subjective point of view [48]. There are many studies affirming that the success of a prosthetic treatment is related to survival, its biocompatibility, and, finally, to patient satisfaction [44,49].…”
Section: Discussionmentioning
confidence: 81%
“…Another documented variable in the present study is patient satisfaction, which is crucial for evaluating the quality of treatment and clinical results from a subjective point of view [48]. There are many studies affirming that the success of a prosthetic treatment is related to survival, its biocompatibility, and, finally, to patient satisfaction [44,49].…”
Section: Discussionmentioning
confidence: 81%
“…The patient satisfaction records in both groups throughout the clinical trial demonstrated how the proper placement & distribution of the implants would affect the quality of the obtained prosthesis, whatever the placement technique utilized in the construction of the progressively loaded prosthesis. [37,38] Regarding Prosthetic Fitness as well as Prosthesis comfort (in terms of stability during rest and function without any patient discomfort), it was revealed that both were insignificantly decreased over time in both groups, and this could be attributed to the continuous stabilization process of the tissues underneath the prostheses over time. On the contrary, the prosthetic maintenance was insignificantly increased in both groups over time, due to increased patients' awareness regarding oral hygiene measures thorough out the investigation period.…”
Section: Discussion Of Resultsmentioning
confidence: 95%
“…Quanto ao ano de publicação, os anos de 2019 6,8,11,16,21-27 e 2018 [28][29][30][31][32][33][34][35][36][37][38] tiveram o maior número de artigos, onze em cada ano; seguidos de 2015 com sete artigos publicados 14,[39][40][41][42][43][44] , 2020 com cinco [45][46][47][48][49] , 2017 com quatro 1-52 , 2010 [53][54][55] , 2012 [56][57][58] , 2014 2,59,60 e 2016 15,61,62 com três artigos cada; 2005 63,64 , 2011 65,66 e 2013 7,67 com dois artigos cada ano, e 2008 12 com apenas um artigo publicado.…”
Section: Resultsunclassified